Avaliação tridimensional do suporte ósseo de dentes posteriores mesializados sobre áreas edêntulas - Estambassi Silva, Lucas (2016)
The mechanics of tooth movement triggers changes periodontal (gum, periodontal ligament and alveolar bone). Generally, when performing the translatory movement of the edentulous ridge region happens to reformulate this favorably. However, very little is known about the possibility of periodontal damage tooth transferred over this region of atrophic edge. Objective: Evaluate the thickness of the buccal bone mace and level of the buccal and lingual crest of posterior teeth after orthodontic treatment for edentulous area. Methods: The sample consisted of 8 subjects, 4 men and 4 women in active orthodontic treatment who had lost at least one posterior tooth. In total they were obtained 18 edentulous sites (9 sites in the maxilla and mandible in 9 sites) which were partially occupied by posterior teeth mesializados orthodontic treatment with the aid of mini-implants. For analysis of bone dimensions around the mesializado tooth tomographic cone beam were used before (T1) and after (T2) orthodontic tooth movement. Imaging studies were performed on CT of type i-CAT ™ (120 kVp, 12mA, voxel 0.2 mm and length of 40 seconds of exposure). Patients were positioned in the device with the position of the head so that the Frankfort plane parallel stay and the median sagittal plane perpendicular to the ground. All measurements were performed in the i-CAT ™ in parasagittal and evaluated cuts on the buccal and lingual surfaces. The comparison between the initial and final heights thicknesses were compared using statistical test "t" paired. Results: There was a statistically significant difference between the initial and final tomographic analysis when assessed levels of buccal and lingual bone crest, unlike the buccal and lingual bone thickness. Conclusion: Teeth displaced over edentulous areas have bony crests considerably displaced apical however this shift does not compromise this therapeutic indication